Review of Exploring L1-L2 relationships: The impact of individual differences by Richard Sparks - Biedroń, Adriana (Studies in Second Language Learning and Teaching, 2023)
This paper is a review of Richard Sparks' latest position, Exploring L1-L2 relationships. The impact of individual differences, which summarizes 30 years of his research in the field of SLA. The author is the originator of the Linguistic Coding Deficit Hypothesis (LCDH), later modified to the Linguistic Coding Differences Hypothesis, which is one of the most cited theories in the context of research into foreign language aptitude. The volume contains 7 chapters representing different strands of research.